Alzheimer’s disease and multiple sclerosis: a possible connection through the viral demyelinating neurodegenerative trigger (vDENT) - Boukhvalova, Marina S.; Kastrukoff, Lorne; Blanco, Jorge C. G. (Frontiers in Aging Neuroscience, 2023)
Alzheimer’s disease (AD) and multiple sclerosis (MS) are two CNS disorders affecting millions of people, for which no cure is available. AD is usually diagnosed in individuals age 65 and older and manifests with accumulation of beta amyloid in the brain. MS, a demyelinating disorder, is most commonly diagnosed in its relapsing-remitting (RRMS) form in young adults (age 20–40). The lack of success in a number of recent clinical trials of immune- or amyloid-targeting therapeutics emphasizes our incomplete understanding of their etiology and pathogenesis. Evidence is accumulating that infectious agents such as viruses may contribute either directly or indirectly. With the emerging recognition that demyelination plays a role in risk and progression of AD, we propose that MS and AD are connected by sharing a common environmental factor (a viral infection such as HSV-1) and pathology (demyelination). In the viral DEmyelinating Neurodegenerative Trigger (vDENT) model of AD and MS, the initial demyelinating viral (e.g., HSV-1) infection provokes the first episode of demyelination that occurs early in life, with subsequent virus reactivations/demyelination and associated immune/inflammatory attacks resulting in RRMS. The accumulating damage and/or virus progression deeper into CNS leads to amyloid dysfunction, which, combined with the inherent age-related defects in remyelination, propensity for autoimmunity, and increased blood-brain barrier permeability, leads to the development of AD dementia later in life. Preventing or diminishing vDENT event(s) early in life, thus, may have a dual benefit of slowing down the progression of MS and reducing incidence of AD at an older age.